Prediction of Confined Blast Loading in Single-Layer Lattice Shells. Issue 7 (July 2014) - Ma, J.L.; Wu, C.Q.; Zhi, X.D.; Fan, F.
Single-layer lattice shells (also known as gridshells) are widely used for architecturally innovative structures. When an explosion occurs inside such a structure, confined blast loading on the structural components will be seriously affected by different factors, such as charge locations and weight, structural types and forms. Moreover, slight changes of blast loading perhaps result in various responses for such a complicated structure. In this paper, blast loads on single-layer lattice shell are calculated by AUTODYN software package. The effect of scaled distance, ratio of rise to span and ratio of height to span are investigated. Simplification of blast loading is studied, and the principles of equivalent loading process are validated with a 40 meters single-layer Kiewitt-8 reticulated dome. In order to predict the blast loading, a precise and simple model is derived from numerical results, which is suitable for a wide scope of single-layer lattice shells. Two applications with different charge weight, structural spans and forms are worked out by using the blast prediction model. Good agreements of comparisons are achieved between prediction model and numerical results.